HEAT TRANSFER COEFFICIENT AND FRICTION FACTOR CHARACTERISTICS OF A GRAVITY ASSISTED BAFFLED SHELL AND HEAT-PIPE HEAT EXCHANGER - P. Raveendiran (Journal of Engineering Science and Technology, 2015)
The heat transfer coefficients and friction factors of a baffled shell and heat pipe heat exchanger with various inclination angles were determined experimentally; using methanol as working fluid and water as heat transport fluid were reported. Heat pipe heat exchanger reported in this investigation have inclination angles varied between 15o and 60o for different mass flow rates and temperature at the shell side of the heat exchanger. All the required parameters like outlet temperature of both hot and cold side of heat exchanger and mass flow rate of fluids were measured using an appropriate instrument. Different tests were performed from which condenser side heat transfer coefficient and friction factor were calculated. In all operating conditions it has been found that the heat transfer coefficient increases by increasing the mass flow rate and angle of inclination. The reduction in friction factor occurs when the Reynolds number is increased. The overall optimum experimental effectiveness of GABSHPHE has found to be 42% in all operating conditioning at ψ = 45o.